Characteristics of sports injuries in athletes during the Winter Olympics: A systematic review and meta-analysis - Wu, Y.; Dai, R.; Yan, W.; Ren, S.; Ao, Y. (Orthopaedic Journal of Sports Medicine, 2024)
Background: Athletes in the Winter Olympic Games are subject to high injury rates given the physical demands of sports. Com prehensive data regarding injury characteristics in these athletes are limited.